2014
DOI: 10.1016/j.nlm.2014.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Increased long-term potentiation at medial-perforant path-dentate granule cell synapses induced by selective inhibition of histone deacetylase 3 requires Fragile X mental retardation protein

Abstract: Non-selective inhibition of histone deacetylases (HDACs), enzymes that remove acetyl groups from histone core proteins, enhances cognition and NMDAR-dependent long-term potentiation at hippocampal CA3-CA1 synapses. It is not known whether this is a general mechanism by which HDACs modulate plasticity at other hippocampal synapses. Furthermore, it has yet to be tested whether HDAC inhibition can reverse deficits in synaptic plasticity in disease models. Here, we investigated whether inhibition of HDACs, and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
5
4
0
Order By: Relevance
“…We began by examining synaptic function in the gene knockout Fmr1-null mouse using ex vivo hippocampal slice physiology. In agreement with prior work (Franklin et al, 2014;Godfraind et al, 1996;Hu et al, 2008;Lauterborn et al, 2007), we find that CA3 Schaffer collateral to CA1 synaptic efficacy and potentiation does not differ between WT and Fmr1-KO brain slices taken from task-naïve mice (Fig. 1).…”
Section: Exaggerated Baseline and Learning-induced Changes Of Synaptisupporting
confidence: 93%
See 1 more Smart Citation
“…We began by examining synaptic function in the gene knockout Fmr1-null mouse using ex vivo hippocampal slice physiology. In agreement with prior work (Franklin et al, 2014;Godfraind et al, 1996;Hu et al, 2008;Lauterborn et al, 2007), we find that CA3 Schaffer collateral to CA1 synaptic efficacy and potentiation does not differ between WT and Fmr1-KO brain slices taken from task-naïve mice (Fig. 1).…”
Section: Exaggerated Baseline and Learning-induced Changes Of Synaptisupporting
confidence: 93%
“…However, the present findings appear incompatible with disruption hypotheses and strongly support alternative hyperstable/discoordination hypotheses for the consequences of FMRP loss in a neural circuit leading to intellectual disability in FXS. While we confirmed that Schaffer collateral synaptic transmission and plasticity are indistinguishable between naïve WT and Fmr1 KO brain slices as previously reported (Franklin et al, 2014;Godfraind et al, 1996;Hu et al, 2008;Lauterborn et al, 2007), we also uncovered substantial abnormalities in the mutant mice, but only after spatial experience (Fig. 1).…”
Section: Fmr1-null Micesupporting
confidence: 90%
“…Therefore, to determine whether heightened dendritic depolarization during LTP inducing stimulation might be linked with the increased LTP magnitude at MPP-DGC synapses, we assessed steady-state depolarization in 6 month TgF344-AD rats compared to WT littermate controls (Fig. 4), and analyzed this in two ways, as we have done previously (Franklin et al, 2014; Smith and McMahon, 2006). We measured the deflection from baseline at 170 msec after the stimulus artifiact when the deflection is stable, and also measured area under the curve (AUC).…”
Section: Resultsmentioning
confidence: 99%
“…Although this study clearly demonstrates that Per1 is an important gene through which HDAC3 regulates long-term memory in the aging brain, other genes most likely contribute to the memory-enhancing effects of HDAC3 deletion. Other genes proposed to mediate the effects of HDAC3 on synaptic plasticity and memory include NF-κB 34 , FMRP 37 , and Nr4a2 26 . In the current study, we identified an additional three genes (Fig.…”
Section: Discussionmentioning
confidence: 99%